The Psychotherapy Documentation Primer. - Wiger, Donald E. (Practiceplanners series, 2011)
Everything you need to know to record client intake, treatment, and progress--incorporating the latest managed care, accrediting agency, and government regulationsPaperwork and record keeping are day-to-day realities in your mental health practice. Records must be kept for managed care reimbursement; for accreditation agencies; for protection in the event of lawsuits; to meet federal HIPAA regulations; and to help streamline patient care in larger group practices, inpatient facilities, and hospitals. The standard professionals and students have turned to for quick and easy, yet comprehensive, g.